Claudia and crazy peaches - Martin, Ann M. 1955- (New York : Scholastic, 1994)
When Claudia's wacky Aunt Peaches moves to Stoneybrook, full of fun and expecting a baby, Claudia thinks she will have the time of her life, until one of Peaches' antics gets Claudia in trouble and a fight ends in tragedy.
Primary
Keywords: Babysitters -- Fiction; Babysitters Club (Imaginary organization) -- Fiction